FENOMENA JUDUL DI PERNOVELAN TANAH AIR - Dini Saptariani (Universitas Maritim AMNI Semarang, 2022)
This article is a literature review on the phenomenon of titles in Indonesian novels. This study is motivated by the phenomenon of the title of the novel which is something that is interesting to study because the author of the novel has put in the time and energy to make a good story but everything can be conveyed to the reader through the intermediary of the title. In addition, titles have extraordinary market power, titles can increase book sales, and generally someone chooses to read through the title. In addition, this article provides information on how to make interesting novel titles and the need to study novel titles from generation to generation of Indonesian literature where the title reflects the contents of the novel and the contents of the novel are influenced by the conditions of society in the era, so if you want to make a bombastic novel title, follow the era and pay attention to taste. market.